DESENVOLVIMENTO DE LIPOSSOMAS COM CREATINA E PENTOXIFILINA E AVALIAÇÃO DA ATIVIDADE BIOLÓGICA NO SÊMEN HUMANO - Pereira, Rafael (2023)
Male infertility is a public health problem that often ends up without diagnosis and specific treatment. It is estimated that the male factor is responsible for up to 40% of infertility cases among couples worldwide. The male gamete, known as sperm, is composed of head, midpiece and tail. The middle piece is rich in mitochondria that are responsible for the energy supplied to the tail, to ensure progressive movement towards the oocyte. Asthenozoospermia is a pathological condition given by several factors, in which the sperm has little or no movement to complete fertilization. In this work, it is hypothesized that low motility is a problem associated with mitochondrial ATP levels. Creatine is a compound of three amino acids widely used as an ergogenic resource in sports because it has the ability to form Creatine Phosphate (PCr) in the mitochondria and increase ATP resynthesis. We question whether the use of Creatine can be an ally in an attempt to improve sperm mitochondrial ATP levels, with consequent increase in motility, resulting in possible success in fertilization. Just like Creatine, Pentoxifylline has features that can supply gametes to the point of improving their motility. In this work, we applied the actives in free form and together in the nanostructure developed in the form of liposome vesicles. Liposomes are lipid vesicles used in conjunction with nanotechnology to increase the stability, viability and bioavailability of molecules such as drugs. In an attempt to improve the parameters that are related to low sperm motility, we used liposomes with Creatine, Pentoxifylline, and the association of the two assets in a single nanostructure. The liposome production method was ethanol injection, which resulted in liposomes with a mean diameter of 124.5 nm, polydispersion index of 0.141 and zeta potential of -3.9 mV. With the production of liposomes, it was possible to validate a chromatographic method for the quantification of Creatine and Pentoxifylline. To assess the effects of treatments on spermatozoa, we analyzed some biochemical parameters: lactate dehydrogenase (LDH) dosage; cell viability test (MTT); dosage of nitric oxide (NO); ATP dosage and eosin nigrosin test, all these parameters showed better results (increasing their levels or not showing significant reduction) in the tests with liposomes or free actives in relation to the control group.